Avaliação da sobrevivência e crescimento de Listeria monocytogenes e Staphylococcus aureus em queijo de coalho durante armazenamento sob baixas temperaturas - Arruda, Maria Digian de Oliveira (2016)
The coalho cheese characterized as a minimally ripened cheese is a typical food manufactured in various states of the Brazilian Northeast region. This product may be a favorable substrate to the survival and growth of pathogenic bacteria because its high pH and moisture content as compared with ripened cheeses. Some studies have detected high counts of Staphylococcus aureus and presence of Listeria monocytogenes in coalho cheese samples. These bacteria are well-known hazards for microbial safety of minimally ripened cheeses in various countries. This study evaluated the survival and growth of strains of L. monocytogenes (ATCC 7644 and ATCC 19115) and S. aureus (ATCC 13565 and ATCC 19095), which were previously adapted to specific antibiotics, in coalho cheese during 14 days as affected by the type of strain, the dose of contamination (3 and 5 log CFU/g) and the storage temperature (7.5 and 12 ºC). Changes in physicochemical parameters in contaminated cheese samples were also assessed over time. The populations of all tested strains were increased by the end of the storage period at 7.5 and 12 ºC. The population of L. monoytogenes and S. aureus assessed increased earlier when the cheese samples were stored at 12 ºC. Populations of 3.9 - 6.2 and 4.3 – 6.4 log CFU/g for L. monocytogenes, and of 4.1 – 6.0 and 4.2 - 6.4 log CFU/g for S. aureus, were detected on the 14th day of storage at 7.5 and 12 ºC, respectively. Minor changes in pH and titratable acidity were verified over time in contaminated cheese samples. These results indicate that L. monocytogenes and S. aureus can survive and grow in coalho cheese stored at 7.5 or 12 ºC, but the growth occur earlier when the cheese is stored at 12 ºC. Therefore, the adoption of good manufacture practices and strict control of refrigeration temperatures during storage are essential to a avoid the contamination and retard the growth of L. monocytogenes and S. aureus in coalho cheese decreasing the risks for occurrence of foodborne diseases associated with the consume of this product. Key-word: Minimally ripened cheese. Microbial behavior. Listeria spp.. Staphylococcus spp.. Food safety.